Central Bank accountability and transparency: theory and some evidence - Sylvester C. W. Eijffinger; Marco Hoeberichts (Deutsche Bundesbank, 2000)
The first part of this paper outlines the concept of democratic accountability of central banks, and compares the legal accountability of the ECB with some other central banks (Bank of Canada, Bank of Japan, Bank of England and the Federal Reserve System). In the second part, we present a theory of central bank accountability. Two aspects of accountability are considered: transparency of actual monetary policy and the question of who bears final responsibility for monetary policy. The paper shows that accountability through transparency leads to a lower expected rate of inflation and less stabilization of supply shocks. Accountability through shifting final responsibility in the direction of the government leads to higher inflationary expectations and more stabilization of supply shocks. – – Der erste Teil dieses Papiers umreißt das Konzept der demokratischen Rechenschaftslegung von Zentralbanken und vergleicht die gesetzlich festgelegte Rechenschaftspflicht der EZB mit der einiger anderer Zentralbanken (Bank of Canada, Bank of Japan, Bank of England und Federal Reserve System). Im zweiten Teil stellen wir eine Theorie über die Rechenschaftspflicht der Notenbanken vor. Dabei werden zwei Aspekte der Rechenschaftspflicht in Betracht gezogen: die Transparenz der aktuellen Geldpolitik und die Frage, wer die endgültige Verantwortung für die Geldpolitik trägt. Das Papier zeigt auf, dass die Rechenschaftspflicht mittels Transparenz zu einer erwarteten niedrigeren Inflationsrate und einer geringeren Stabilisierung von Angebotsschocks führt. Dagegen führt die Rechenschaftspflicht mittels Verlagerung der endgültigen Verantwortung hin zur Regierung zu höheren Inflationserwartungen und einer stärkeren Stabilisierung von Angebotsschocks.
Keywords: E58; E52; 330; monetary policy; central banks; transparency; accountability; Geldpolitik; Publizitätspflicht; Zentralbank; Auskunftspflicht; Inflationserwartung; Schätzung; Theorie; Kanada; Japan; Großbritannien; USA; EU-Staaten